Characterization of CRISPR-Cas systems in Bifidobacterium breve. Issue 4 (22nd April 2022) - Han, Xiao; Zhou, Xingya; Pei, Zhangming; Stanton, Catherine; Ross, R. Paul; Zhao, Jianxin; Zhang, Hao; Yang, Bo; Chen, Wei
Abstract : The clustered regularly interspaced short palindromic repeat (CRISPR)-CRISPR-associated protein (Cas) system is an important adaptive immune system for bacteria to resist foreign DNA infection, which has been widely used in genotyping and gene editing. To provide a theoretical basis for the application of the CRISPR-Cas system in Bifidobacterium breve, the occurrence and diversity of CRISPR-Cas systems were analysed in 150 B. breve strains. Specifically, 47 % (71/150) of B. breve genomes possessed the CRISPR-Cas system, and type I-C CRISPR-Cas system was the most widely distributed among those strains. The spacer sequences present in B. breve can be used as a genotyping marker. Additionally, the phage assembly-related proteins were important targets of the type I-C CRISPR-Cas system in B. breve, and the protospacer adjacent motif sequences were further characterized in B. breve type I-C system as 5′-TTC-3′. All these results might provide a molecular basis for the development of endogenous genome editing tools in B. breve .